Zum syntaktisch-semantischen Status adverbialer Äußerungsglieder - Ogawa, Akio (Studia Germanica Posnaniensia, 2018)
In this article I attempt to show that grammatical categories such as the adverbs dabei (with it/them) and doch (but, still) in German can be explained as prosodic, syntactic, semantic and pragmatic continuum based on their core meaning. Some classifications described and maintained in the traditional grammar of German, especially represented by the „valency grammar“, i.e. classifications as „sentential adverbs“ or „discourse markers“, therefore should be neutralized and newly considered. The grammatical categories in charge should be understood as crossing over the unit of sentence, and in this respect they are not „Satzglieder“ (sentence constituents), but „Äußerungsglieder“ (utterance constituents) as Darski (2010) claims. In the „adverbial“ area prosodic features and syntactic positions closely correspond to each other and on the other hand semantic contents and pragmatic effects do correspond too. The continuous scale of the elements dabei and doch can be seen as an ample example for demonstrating the „iconic“ relation between prosody/syntax and semantics/pragmatics, i.e. between forms and functions.